2015
DOI: 10.1097/aud.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Predictors of Longitudinal Hearing Aid Use for Children Who Are Hard of Hearing

Abstract: Objectives-Children who are hard of hearing (CHH) have restricted access to acoustic and linguistic information. Increased audibility provided by hearing aids (HAs) influences language outcomes, but the advantages of appropriately-fit HAs can only be realized if children wear their devices on a consistent basis. The purpose of the current paper was to characterize long-term HA use in CHH, based on parent report measures, and identify factors that influence longitudinal trends in HA use.Design-Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 35 publications
7
73
1
3
Order By: Relevance
“…Data concerning daily HA use were obtained via a parent questionnaire (see Walker et al this issue, pp. XXX and Walker et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Data concerning daily HA use were obtained via a parent questionnaire (see Walker et al this issue, pp. XXX and Walker et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…XXXX), consistently-worn amplification (Tomblin et al, this volume, pp. XXXX; Walker et al, this volume, pp. XXXX), and provision of high quality language exposure in the home (Ambrose et al, this volume, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that hearing aid (HA) use is highly variable in infants and toddlers (Marnane & Ching 2015; Muñoz et al, 2014, 2015; Walker et al 2015). For example, it has been shown that children between 6 months and 2 years of age use their HAs for an average of 4.36 hours per day; whereas, pre-school children between the ages of 2 and 4 years wear their hearing aids on average 7.5 hours per day (Walker et al 2015). While there is no comparison regarding wear time in the literature between children younger than 3 years who use HAs and children who wear CIs, recent unpublished data on CI use in young children also show variable use (Tournis, Reference Note 1).…”
Section: Discussionmentioning
confidence: 99%